The Figure of the “Climate Refugee” in Inger Elisabeth Hansen’s Å resirkulere lengselen: avrenning foregår (2015) - Jenna Coughlin (Scandinavian-Canadian Studies, 2018)
ABSTRACT: This article addresses the Norwegian response to global climate change and increased human migration through an analysis of the figure of the “climate refugee” in Inger Elisabeth Hansen’s 2015 poetry collection, Å resirkulere lengselen, avrenning foregår. In addition to situating the work in the context of the so-called “refugee crisis,” the author also discusses the origins of the term “climate refugee” and the conceptual and ethical problems surrounding such a designation. The article examines notions of aesthetics and poetics in the text, arguing that Hansen draws attention to the ubiquity of risk in the history of cultural exchange between humans. Rather than a poetics that attempts to manage mobile bodies or eliminate risk, the author argues that Hansen advocates for a poetics of relation that takes its inspiration from dynamic forms in nature.